Engineering Gene Therapy: Advances and Barriers (Adv. Therap. 9/2021). Issue 9 (21st September 2021) - Shahryari, Alireza; Burtscher, Ingo; Nazari, Zahra; Lickert, Heiko
Abstract : Recent progresses in discovery, development and exploitation of gene manipulation and delivery tools have dramatically revolutionized the gene therapy field for modern therapies. Alireza Shahryari, Ingo Burtscher, Zahra Nazari and Heiko Lickert summarize and discuss the advances and barriers of the gene editing platforms, viral gene delivery vehicles and non‐viral molecular tools in a comprehensive review article, in article number 2100040 .